LINGUISTIC PROBLEMS OF ENGLISH LEXICOGRAPHY (Journal of Universal Science Research, 2023)
Even though a great number of researches has been carried out on Lexicography for a long time, there is still need for investigating much more on this field. Because English language  is consonantly developing minute by minute, we need to work with dictionaries. This article is devoted to provide some data about the linguistic issues on English lexicography.